Bilateral agreement for the academic year 2011-2013 LLP Programme: Higher Education Erasmus between Universidade Lusíada de Lisboa and Universidad de Castilla-La Mancha - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP/Erasmus programme; - Subject area: Social work and counselling; Law.